Partisipasi Masyarakat dalam Pengelolaan Mandiri Pariwisata Berbasis Komunitas: Studi Kasus Pantai Mlarangan Asri - Ihsanuddin, Ihsanuddin; Salisul Khakim, Muhammad (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
In recent years, Mlarangan Asri Beach has developed into a tourist destination that is fully managed by the community through the Tourism Awareness Group (Pokdarwis) without direct involvement from the local government in terms of funding. The experience of Pokdarwis Mlarangan Asri shows that tourism development does not always require structural intervention from outside, but can grow from the strength of the local community. This study aims to describe and analyze the forms of community participation in the independent management of the Mlarangan Asri Beach tourist attraction. This study uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews, participatory observation, and documentation. The sources consist of Pokdarwis administrators, village officials, MSME actors, and the local community. The results of the study show that community participation is reflected in four dimensions, namely decision-making through regular deliberation forums, operational implementation based on the division of tasks within the Pokdarwis structure, fair utilization of results through parking and MSME revenues, and periodic evaluations involving administrators and residents. This study concludes that management is carried out independently without dependence on government budgets, but is still able to create positive impacts in terms of social, economic, and community institutional aspects. This study contributes theoretically by proving that autonomous community empowerment, based on social capital and local institutional capacity, is an effective model for independent and sustainable tourism development.